2015
DOI: 10.1088/0964-1726/24/11/115032
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental analysis of a piezoelectric plate connected to a negative capacitance at MHz frequencies

Abstract: In this paper, a theoretical and experimental study of the electric impedance of a piezoelectric plate connected to a negative capacitance is performed in the MHz frequency range. The negative capacitance is realized with a circuit using current conveyors (CCII+). This circuit allows us to achieve important values of negative capacitance, of the same order of the static capacitance of the piezoelectric plate studied. Mason's model is considered for the theoretical characterization of the piezoelectric plate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They have shown that it is possible to considerably modulate the properties of a PC made up of alternating piezoelectric and elastic layers by modifying the electrical boundary conditions of active inclusions. The case of the connexion of an electrical passive load across the piezoelectric element has been investigated, with an electrical open-circuit or short-circuit by Mansoura et al [16,17] in the case of bulk waves and by C. Vasseur et al [18] in the case of guided waves, and with resistive loads by Airoldi et al [19]. Frequency dependant electrical load have also been investigated with a capacitance by Degraeve et al [20][21][22] and Ponge et al [23,24], with an inductance by Mansoura et al [25], and with a resonant parallel LC load by E.A.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that it is possible to considerably modulate the properties of a PC made up of alternating piezoelectric and elastic layers by modifying the electrical boundary conditions of active inclusions. The case of the connexion of an electrical passive load across the piezoelectric element has been investigated, with an electrical open-circuit or short-circuit by Mansoura et al [16,17] in the case of bulk waves and by C. Vasseur et al [18] in the case of guided waves, and with resistive loads by Airoldi et al [19]. Frequency dependant electrical load have also been investigated with a capacitance by Degraeve et al [20][21][22] and Ponge et al [23,24], with an inductance by Mansoura et al [25], and with a resonant parallel LC load by E.A.…”
Section: Introductionmentioning
confidence: 99%
“…In medical applications, piezoelectric sensors can be utilized to detect human body information and perform ultrasound therapy [10][11][12]. When conducting theoretical analysis and research on piezoelectric devices, such as piezoelectric filters and transformers, these devices are typically electrically equivalent to a capacitor in series with a voltage source or a capacitor in parallel with a current source [13][14][15]. That is, piezoelectric structures are usually considered as capacitive elements in current studies.…”
Section: Introductionmentioning
confidence: 99%